Evolutionarily distinct and sperm-specific supersized chromatin loops are marked by Helitron transposons in Xenopus tropicalis - Zhaoying Shi; Jinsheng Xu; Longjian Niu; Wei Shen; Shuting Yan; Yongjun Tan; Xuebo Quan; Edwin Cheung; Kai Huang; Yonglong Chen; Li Li; Chunhui Hou (Cell Reports, 2023)
Summary: Transposable elements (TEs) are abundant in metazoan genomes and have multifaceted effects on host fitness. However, the mechanisms underlying the functions of TEs are still not fully understood. Here, we combine Hi-C, ATAC-seq, and ChIP-seq assays to report the existence of multimegabase supersized loop (SSL) clusters in the Xenopus tropicalis sperm. We show that SSL anchors are inaccessible and devoid of the architectural protein CTCF, RNA polymerase II, and modified histones. Nearly all SSL anchors are marked by Helitrons, a class II DNA transposon. Molecular dynamics simulations indicate that SSL clusters are likely formed via a molecular agent-mediated chromatin condensation process. However, only slightly more SSL anchor-associated genes are expressed at late embryo development stages, suggesting that SSL anchors might only function in sperm. Our work shows an evolutionarily distinct and sperm-specific genome structure marked by a subset of Helitrons, whose establishment and function remain to be explored.